Eigenstructure assignment for linear discrete-time systems subject to input saturation via decentralized state feedback - a parametric approach - Yu Xue; Guang-ren Duan (2005 International Conference on Machine Learning and Cybernetics, 2005)
A parametric approach for eigenstructure assignment for linear discrete-time systems subject to input saturation via decentralized state feedback is proposed. Based on the parametric solution to a Sylvester matrix equation, parameterizations of all the state feedback control matrices and the closed-loop eigenvector matrices are established. The partial eigenstructure assignment is a case of the proposed approach. The parametric method offers all the design degrees of freedom, which can be utilized to achieve certain desired properties and performances in the control system designs. A numerical example shows the effect of the proposed approach.